Unraveling Crime Dynamics in Indonesia: Exploring the Impact of Population Density, Poverty, Average Years of Schooling (RLS), and Open Unemployment Rate (TPT) in Java in 2020 - Anggaresa, Fathanya Puja; Suryana (UIN Sunan Kalijaga Yogyakarta, 2023)
Abstract: The fluctuating crime rate in Indonesia, particularly in the moderate category, highlights the intricate interplay of various factors influencing criminal activities. This research endeavors to uncover the correlations among different variables contributing to crime by utilizing a cross-sectional approach based on secondary data sourced from the 2021 BPS data. The study discerns a positive correlation between population density and the open unemployment rate (TPT) in relation to crime. Conversely, poverty and the average years of schooling (RLS) exhibit a relatively minor impact. During the examination of these relationships, it became evident that the population density variable exerts both direct and indirect influences on crime. The indirect connection is established through the impact of population density on the poverty rate, which subsequently exerts a positive and direct influence on crime. Consequently, it is apparent that population density stands out as the predominant factor influencing the crime rate on Java Island. To address this, interventions targeting the decomposition of population density are essential, particularly through initiatives aimed at fostering increased solidarity. This is imperative because the correlation between population density and poverty, contributing to an escalation in crime, results in a decline in individual trust levels, fostering competition for resource access. This heightened competition, in turn, precipitates struggles that contribute to the emergence of criminal activities. Keyword; socio-economy factors, path analysis, direct effect, indirect effect Abstrak: Penurunan tingkat kriminalitas di Indonesia yang fluktuatif dengan jumlah kriminalitas dalam kategori sedang mencerminkan keragaman faktor yang mendeterminasi tindakan kejahatan. Penelitian ini bertujuan untuk menemukan hubungan antar varibel yang mempengaruhi tindakan kriminalitas dengan menggunakan cross sectional terhadap sumber data sekunder yang diperoleh dari data BPS 2021. Penelitian ini menemukan hubungan positif antara kepadatan penduduk dan tingkat pengangguran terbuka (TPT) terhadap kriminalitas. Sedangkan kemiskinan dan rata-rata lama sekolah (RLS) berpengaruh kecil. Dalam proses pengujian hubungan ditemukan variabel kepadatan penduduk memiliki pengaruh langsung dan tidak langsung terhadap kriminalitas. Hubungan tidak langsung ditemukan melalui pengaruh kepadatan penduduk terhadap tingkat kemiskinan yang berpengaruh positif dan langsung terhadap kriminalitas, sehingga varibel dominan yang mempengaruhi tingkat kejahatan di Pulau Jawa bersumber dari kepadatan penduduk. Intervensi yang dibutuhkan dalam penguraian kepadatan penduduk diperlukan melalui peningkatan solidaritas. Hal ini disebabkan hubungan kepadatan penduduk terhadap kemiskinan yang menyebabkan peningkatan kejahatan berdampak pada pengurangan tingkat kepercayaan individu yang menjadi pendorong persaingan terhadap akses sumber daya. Persaingan ini pada akhirnya memunculkan perebutan yang memunculkan beragama tindakan kriminalitas. Kata Kunci: faktor sosial ekonomi, analisis jalur, pengaruh langsung, pengaruh tidak langsung